In Vitro Antifungal Activity of Ethanolic Stem Extract of Tinospora crispa Against Candida albicans and Malassezia furfur - Mumtaz, Syifa Afifah; Zulfa, Fajriati; Thadeus, Maria Selvester; Setyaningsih, Yuni (BIOEDUSCIENCE, 2025)
Background: Fungal infections such as candidiasis caused by Candida albicans and pityriasis versicolor caused by Malassezia furfur are highly prevalent in Indonesia. Conventional antifungal treatments often face challenges like resistance and adverse side effects. As an alternative, brotowali stem (Tinospora crispa) extract, rich in alkaloids, flavonoids, and tannins, shows promise as an antifungal agent. This research investigates the in vitro antifungal efficacy of ethanol extract from brotowali stem against C. albicans and M. furfur. Methods: A laboratory experimental design utilizing the well-diffusion method was applied, measuring inhibition zone diameters on Sabouraud Dextrose Agar after 2x24 hours at extract concentrations of 45%, 60%, 75%, and 90%. Results: The ethanol extract of brotowali stem exhibited statistically significant but relatively low antifungal activity based on inhibition zone diameters against C. albicans (0,002) and M. furfur (0,001), with higher concentrations showing greater antifungal. The largest inhibition zones measured 5.93 mm for C. albicans and 3.97 mm for M. furfur. Conclusions: The extract concentrations of 90% concentration exhibited moderate antifungal activity against C. albicans. For M. furfur, all concentrations demonstrated weak antifungal activity.